The consensus guideline of perioperative antiviral therapy for AIDS patients in China based on clinical practice - Ma, Rui; Zhang, Qiang; Zhao, Chang song; Zhao, Rugang; Zhang, Yao; Zhang, Yao shen; Hai, Yong; Wei, Guo; Pu, Yu; Hu, Li qiang; Song, Yanzheng; Zhang, Yu; et al. (Frontiers in Medicine, 2023)
The prevalence of human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) has emerged as a major public health concern in China. When patients with HIV infection undergo surgical treatment, there are two main challenges. Firstly, medical staff face a high risk of HIV infection due to occupational exposure. Secondly, the patient’s immune function is impaired, increasing the risk of opportunistic infections and postoperative complications. The surgical treatment of such patients is unique, and the risk of occupational exposure during the operation primarily depends upon the viral load of HIV/AIDS patients. Therefore, perioperative antiretroviral therapy is of paramount importance in order to standardize the perioperative antiretroviral therapy (ART) for HIV/AIDS patients. The Surgery Group of the Chinese Association of STD and AIDS Prevention and Control, in collaboration with the Treatment Association, and Surgery Group of the Chinese Medical Association of Tropical Diseases and Parasitology, has developed an expert consensus on perioperative antiretroviral therapy for HIV/AIDS patients. This consensus encompasses various aspects, including surgical risk assessment, selection of perioperative antiretroviral therapy regimens, prevention of opportunistic infections, and the crucial focus on rapid preoperative viral load reduction and immune function reconstruction for HIV/AIDS patients.